The People's Republic of China's position on Soviet-Yugoslav relations1948-1962 - Azhar Abdulrahman Abdulkarim Al-Lafta, Prof. Dr. (lark, 2025)
Continue reading the research titled (The People's Republic of China's Position on Soviet-Yugoslav Relations 1948-1962). Since its founding, the People's Republic of China has been keen to pursue a foreign policy that strengthens its political standing, given the tensions surrounding bilateral Soviet-Yugoslav relations. The Chinese government supported the Soviet Union's anti-Yugoslav policy and denounced its policies, which were often inconsistent with Marxist socialist principles. The research consists of an introduction, three chapters, and a conclusion. The first addresses the Soviet-Yugoslav dispute and China's position on it from 1948 to 1953. The second examines the impact of Soviet policy on the thaw in Sino-Yugoslav relations from 1953 to 1958. The third chapter focuses on the tensions in Sino-Yugoslav relations from 1958 to 1962. The research concludes that the Soviet factor played a major role in China's position and the changes in that position toward Yugoslavia, which were influenced by changes in Soviet-Yugoslav relations.
Keywords: People's Republic of China, Soviet Union, Yugoslavia, tensions, Titoism , revisionism.